Effects of Novel Calpain Inhibitors in Transgenic Animal Model of Parkinson's disease/dementia with Lewy bodies. Issue 1 (December 2018) - Hassen, Getaw; Kesner, Leo; Stracher, Alfred; Shulman, Abraham; Rockenstein, Edward; Mante, Michael; Adame, Anthony; Overk, Cassia; Rissman, Robert; Masliah, Eliezer
Abstract Parkinson's disease (PD) and dementia with Lewy bodies (DLB) are neurodegenerative disorders of the aging population characterized by the accumulation of α-synuclein (α-syn). The mechanisms triggering α-syn toxicity are not completely understood, however, c-terminus truncation of α-syn by proteases such as calpain may have a role. Therefore, inhibition of calpain may be of value. The main objective of this study was to evaluate the effects of systemically administered novel low molecular weight calpain inhibitors on α-syn pathology in a transgenic mouse model. For this purpose, non-tg and α-syn tg mice received the calpain inhibitors - Gabadur, Neurodur or a vehicle, twice a day for 30 days. Immunocytochemical analysis showed a 60% reduction in α-syn deposition using Gabadur and a 40% reduction using Neurodur with a concomitant reduction in c-terminus α-syn and improvements in neurodegeneration. Western blot analysis showed a 77% decrease in α-spectrin breakdown products (SBDPs) SBDPs with Gabadur and 63% reduction using Neurodur. There was a 65% reduction in the active calpain form with Gabadur and a 45% reduction with Neurodur. Moreover, treatment with calpain inhibitors improved activity performance of the α-syn tg mice. Taken together, this study suggests that calpain inhibition might be considered in the treatment of synucleinopathies.